QTL and Candidate Gene Identification for Silique Length Based on High-Dense Genetic Map in Brassica napus L. - Wang, Hui; Zaman, Qamar U.; Huang, Wenhui; Mei, Desheng; Liu, Jia; Wang, Wenxiang; Ding, Bingli; Hao, Mengyu; Fu, Li; Cheng, Hongtao; Hu, Qiong (Frontiers in Plant Science, 2019)
Silique length (SL) is an important yield trait and positively correlates with seeds per silique and seed weight. In the present study, two double haploid (DH) populations, established from crosses Zhongshuang11×R11 (ZR) and R1×R2 (RR), containing 280 and 95 DH lines, respectively, were used to map QTL for SL. A high dense genetic map from ZR population was constructed comprised of 14658 bins on 19 linkage groups, with map length of 2198.85 cM and an average marker distance of 0.15 cM. Genetic linkage map from RR population was constructed by using 2046 mapped markers anchored to 19 chromosomes with 2217 cM map length and an average marker distance of 1.08 cM. Major QTL qSL_ZR_A09 and qSL_RR_A09b on A09 were identified from ZR and RR populations, respectively. Both QTL could be stably detected in four environments. QTL qSL_RR_A09b and qSL_ZR_A09 were located on 68.5-70.8 and 91.33-91.94 interval with R2 values of 14.99%-39.07% and 15.00%-20.36% in RR and ZR populations, respectively. Based on the physical positions of SNP markers flanking qSL_ZR_A09 and gene annotation in Arabidopsis, 26 genes were identified with SNP/Indel variation between parents and two genes (BnaA09g41180D and BnaA09g41380D) were selected as the candidate genes. Expression analysis further revealed BnaA09g41180D, encoding homologs of Arabidopsis fasciclin-like arabinogalactan proteins (FLA3), as the most promising candidate gene for qSL_ZR_A09. The QTL identification and candidate gene analysis will provide new insight into the genomic regions controlling SL in B. napus as well as candidate genes underlying the QTL.